STUDENTS’ ERRORS IN PRONOUNCING VOICED AND VOICELESS ENGLISH CONSONANTS - Mohamad Yunus Laia (Institut Pendidikan Tapanuli Selatan, 2020)
This research aimed to identify the pronunciation errors made by the second semester of English Language Education Study Program of STKIP Nias Selatan. This research was a kind of qualitative research. The subject in this research was second class (28 students) of the second semester. Meanwhile, the object in this research students’ error in pronouncing voiced and voiceless English consonants made by second semester and the causes of the errors itself. The documentations of students’ pronunciation and interview were used to collect the data of the research.. The result of data analysis showed that; (1) There are some of the errors that students made in pronouncing voiced and voiceless English consonants based on the manner of articulations, such as: error in pronouncing /ʒ/, /ð/, /θ/ and /ʃ/. Students also made errors based on the rules in pronouncing consonants, it was error in pronouncing silent consonants, double consonants, consonants digraph/other combinations, indeed in pronouncing simple consonants students still made the errors. (2) The factors that causes the students error in pronouncing English consonants were: students’ first language, amount of exposure, phonetic ability, motivations, combinations of English sounds, concept of English sound, curriculum of Indonesian, and the last students’ facilities in learning English. It is recommended that the students to practice English a lot especially in pronunciation, and lecturer should be more active and creative to help the students who have difficulty in English pronunciation.